Central Giant Cell Granuloma in Pediatric Maxilla: Surgical Management - Faverani, Leonardo Perez; Ferreira, Sabrina; Ferreira, Gabriel Ramalho; Colete, Juliana Zorzi; Aranega, Alessandra Marcondes [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP] (Lippincott Williams & Wilkins, 2014)
Central giant cell granuloma (CGCG) is an intraosseous lesion consisting of fibrous cellular tissue that contains multiple foci of hemorrhage, multinucleated giant cells, and occasional trabeculae of woven bone. An 8-year-old boy presented himself complaining of a painless swelling in the left maxilla that had started 1 year. Computed tomography (CT) scan confirmed a poorly defined multilocular radiolucent lesion in the left maxilla crossing the midline. The patient underwent enucleation through an intraoral approach of the lesion. The biopsy revealed multinucleated giant cells in a fibrous stroma. A CT was taken approximately 1 year postoperatively. There was no clinical or radiographic evidence of recurrence. Therefore, surgical treatment of CGCG can be performed, trying to preserve the surrounding anatomic structures, which can be maintained in case the lesion does not show an aggressive clinical behavior, avoiding large surgical defects which are undesirable in children.
Keywords: Giant cell; granuloma; children; jaws; treatment